Raw food kitchen : naturally vibrant recipes for breakfast, snacks, mains & desserts - Gulin, Dunja (Ryland Peters & Small, 2012)
More and more people are turning to raw food to give them energy, boost their immune system, clear their skin, lose weight and stay slim. There are so many dishes and ways of working with raw food to create an interesting, sustainable diet, without needing many hard-to-find ingredients or hours of preparation